2005
DOI: 10.1111/j.1365-313x.2005.02556.x
|View full text |Cite
|
Sign up to set email alerts
|

Consistent transcriptional silencing of 35S‐driven transgenes in gentian

Abstract: SummaryIn this study, no transgenic gentian (Gentiana triflora · Gentiana scabra) plants produced via Agrobacteriummediated transformation exhibited transgene (GtMADS, gentian-derived MADS-box genes or sGFP, green fluorescent protein) expression in their leaf tissues, despite the use of constitutive Cauliflower mosaic virus (CaMV) 35S promoter. Strikingly, no expression of the selectable marker gene (bar) used for bialaphos selection was observed. To investigate the possible cause of this drastic transgene sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 48 publications
(77 reference statements)
3
87
0
4
Order By: Relevance
“…Takashi Nakatsuka, Kei-ichiro Mishiba a , Yoshiko Abe, Akiko Kubota, Yuko Kakizaki, Saburo Yamamura, Masahiro Nishihara * that the CaMV35S promoter underwent strong gene silencing by sequence-specific DNA methylation in gentian plants (Mishiba et al 2005). By screening several promoters, we found that the Agrobacterium rhizogenes rolC promoter could avoid gene silencing and induce semi-constitutive gene expression in transgenic gentian plants (Mishiba et al 2005).…”
Section: Flower Color Modification Of Gentian Plants By Rnai-mediatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Takashi Nakatsuka, Kei-ichiro Mishiba a , Yoshiko Abe, Akiko Kubota, Yuko Kakizaki, Saburo Yamamura, Masahiro Nishihara * that the CaMV35S promoter underwent strong gene silencing by sequence-specific DNA methylation in gentian plants (Mishiba et al 2005). By screening several promoters, we found that the Agrobacterium rhizogenes rolC promoter could avoid gene silencing and induce semi-constitutive gene expression in transgenic gentian plants (Mishiba et al 2005).…”
Section: Flower Color Modification Of Gentian Plants By Rnai-mediatedmentioning
confidence: 99%
“…By screening several promoters, we found that the Agrobacterium rhizogenes rolC promoter could avoid gene silencing and induce semi-constitutive gene expression in transgenic gentian plants (Mishiba et al 2005). Sugaya and Uchimiya (1992) have reported that the activity of the rolC promoter was localized predominantly in vascular bundle tissues of transgenic tobacco plants.…”
Section: Flower Color Modification Of Gentian Plants By Rnai-mediatedmentioning
confidence: 99%
“…More than half the phenotypes are from Arabidopsis. The efficiency of induction of abnormal phenotypes was high in Arabidopsis (257 phenotypes by 50 TFs) and morning glory (36 phenotypes by 11 TFs), while in gentian (4 phenotypes by 23 TFs) it was low, probably because of gene silencing of the transgene (Mishiba et al 2005;Mishiba et al 2010). In ornamental plants, flower phenotypes, especially in the petals, were frequently observed because the petals of ornamental plants are conspicuous and modification of the petal is the main focus of our project.…”
Section: Finding a Tf That Induces A Phenotype Of Interestmentioning
confidence: 92%
“…Transformation methods of Torenia (Aida and Shibata 2001), Chrysanthemum (Aida et al 2004), Pharbitis and Gentiana (Mishiba et al 2005) were described previously. Improved method of transformation of Cyclamen is reported in this issue (Terakawa et al 2008).…”
Section: Plant Transformationmentioning
confidence: 99%
“…Multi-copied endogenous genes may be a major obstacle in applying CRES-T, even though CRES-T has great potential to overcome gene redundancy. In gentiana, every gene construct was driven by the promoter of the Arabidopsis ACTIN2 (ACT2) gene (An et al 1996) instead of the CaMV 35S promoter, because the 35S promoter is known to be extensively methylated and inactivated in gentiana (Mishiba et al 2005 kinds of them were mixed in Arabidopsis. From each batch, we grew approximately 200 independent transformants and examined phenotypes individually (Table 2).…”
mentioning
confidence: 99%